Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

a person invests 1000 at a bank at 4 percent compound interest compounded annually and every year government and bank charges amounting to C are deducted and if An is the value of the investment at the end of 10 years.

Solve this difference equation.

if i)C=0 ii)C=40

$$ A_{10} = 1.04 A_{n-1} - C $$
$$ A_0 = 1000 $$

i) C=0

$$ A_{10} = 1.04^{10} . 1000 = 1480.24 $$

ii) C=40

$$ A_n = 1.04 . A_{n-1} - 40 $$

Particular solution: Put $$ A_n = A_{n-1} = A* $$
$$ A* = 1.04 . A* - 40 $$
$$ A* = 40/0.04 = 1000 $$

General solution of the associated homogenous equation: $$ A_n = 1.04 A_{n-1} $$
$$ a_n = A . 1.04^n $$

General solution of the difference equation: $$ A_n = A_n + A* $$
$$ A_n = A . 1.04^n + 1000 $$
$$ A_0 = A . 1.04^0 + 1000 $$
$$ A = 1000 $$

$$ A_{10} = 1000 . 1.04^{10} + 1000 $$
$$ = 1480.20 + 1000 $$
$$ = 2480.24 $$

Getting 2480.24 as the answers tell me something is wrong. But I cant figure out which part of my working is incorrect.

Since 1000-40 for 10 years I believe the answer should be

$$ A_{10} = 1.04^{10} . 1000 - 40 $$

Please advise.

share|improve this question
2  
In your first line the subscript $10$ should be $n$, and why is the multiplier $1.04$ instead of $1.02$? This ripples all the way through. –  Ross Millikan May 2 '11 at 17:44
    
i have updated to 4 percent. Can anyone explain the concept of particular solution, general solution to linear recurrence equation? –  optimus May 3 '11 at 12:14
add comment

3 Answers 3

up vote 2 down vote accepted

I propose that we deal with this problem in a purely algebraic fashion, i.e., without talking about specific numbers like 4% or $40\$$ or 10 years. So we have an initial investment $a_0$ on January 1st of year 1, an annual increment factor $1+p$ and an annual charge $c$. After $n$ years have elapsed, i.e., on January 1st of year $n+1$, the amount on the account is $a_n$. The sequence $n\mapsto a_n$ satisfies the recurrence relation $$a_{n+1}=(1+p)a_n - c\qquad(n\geq 0)\ .$$ If it weren't for the $c$ the $a_n$ would increase exponentially. To account for the charges we try a solution of the form $$a_n= a (1+p)^n + b\qquad (n\geq 0)\qquad(*)$$ and hope that we can fix the constants $a$ and $b$ in such a way that all conditions of the problem are fulfilled.

Putting $n=0$ in $(*)$ we must have $a+ b=a_0$ (where $a_0$ is given in advance), and the recurrence relation implies $$a(1+p)^{n+1} + b = (1+p)\bigl(a(1+p)^n + b \bigr) -c$$ from which we draw the condition $b=(1+p) b -c \ $ or $\ b={c\over p}$. It follows that $a=a_0-{c\over p}$ so that we definitively obtain $$a_n=\Bigl(a_0-{c\over p}\Bigr)(1+p)^n + {c\over p}\ .$$

share|improve this answer
add comment

Your work on i.) is correct. For ii.) you could just notice that with $C=40, A_0=1000$, you get $A_1=1000$ and nothing changes. So $A_n=1000$ for all $n$. If $A_0$ were not $1000$, you could imagine breaking $A_0$ into two pieces-$A_*$ and $A_{**}$. The $A*$ piece, we see, doesn't change and pays the annual fee of $C$. The $A_{**}$ piece (which could be negative) is left to grow at $4\%$ per year. So if you started with $A_0=1500$ you would say $A_*=1000, A_{**}=500,$ so $A_n=1000+500\cdot1.04^n$. Have you checked out the Wikipedia article?

share|improve this answer
    
$$ A_0 = A(1.04)^0 + 1000 $$ $$ A = 1000 $$ Hence $$ A = 0 $$ $$ A_10 = 1000 $$ –  optimus May 3 '11 at 12:56
    
I dont really understand the explanations on wikipedia. –  optimus May 3 '11 at 12:57
    
can anyone further elaborate? –  optimus May 3 '11 at 14:31
    
@liengteh: Do you understand the separation into a particular solution of the full equation and a general solution of the homogeneous equation (deleting your C) because of linearity? That is the heart of this. –  Ross Millikan May 5 '11 at 4:46
add comment

In general: We know the recurrence:

$a_{n+1} = r \; a_n $

has the explicit solution

$a_n = r^n a_0$

To solve the non-homogeneous recurrence

$a_{n+1} = r \; a_n + c $

we seek an alternative $b_n = a_n + x$ ($x$ is to be found) such that the above equation is equivalent to

$b_{n+1} = r \; b_n $

Replacing, we must have $c = rx -x$, so $x = c/(r-1)$

And then the solution is

$b_n = r^n \; b_0$

$a_n + x = r^n \; ( a_0 + x)$

$\displaystyle a_n = r^n \; a_0 + c \frac{ r^n-1}{r-1}$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.